OKSIDASI NITRIT OLEH BAKTERI HETEROTROFIK PADA KONDISI AEROBIK - Agustiyani, Dwi; Kayadoe, Ruly Marthina; Imamuddin, Hartati (JURNAL BIOLOGI INDONESIA, 2010)
ABSTRACTNitrite Oxidation by Heterotrophic Bacteria Under Aerobic Condition. The nitrite transformingactivities of heterotrophic bacteria from isolates from agriculture soil, Lampung were studiedunder aerobic conditions. Among the 9 bacterial isolates tested, almost all are reported haveability to consume of nitrite, but none of the bacterial isolates formed significant nitrate in themedium. NOB H1 (Bacillus licheniformis), is denitrification-negative, consumed 16. 4 mg/L ofnitrites with the accumulation of 4.45 mg/L nitrates. While, NOB H8 (Pseudomonas sp.) isdenitrification-positive, consumed 49. 64 mg/L of nitrite with the accumulation of 3.34 mg/Lnitrates. Nitrite oxidations of both isolates NOB H1 and NOB H8 took place during stationeryphase to the dead phase. Growth pattern of both isolates NOB H1 and NOB H8 were sigmoidwith generation time of 1.69 and 2.19 hour, respectivelyKey words: heterotrophicbacteria; nitrite oxidation; denitrification